Optimization of zinc‐nickel film electrodeposition for better corrosion resistant characteristics. (16th July 2019) - Anwar, Shams; Khan, Faisal; Zhang, Yahui; Caines, Susan
Abstract : Corrosion is one of the main causes of structural deterioration in offshore and marine structures. One way to mitigate the effect of corrosion is with Zn‐Ni electroplated coatings. An experimental design and optimization procedures for Zn‐Ni alloy electroplating was an explored. This study analyzed a five‐variable experimental plan comprised of four steps: (1) a two‐level fractional factorial design (FFD); (2) a response surface design the steepest ascent analysis; (3) a central composite design (CCD); and (4) a corrosion behaviour test to optimize the factors in Zn‐Ni deposition. The critical plating variables in step 1 were zinc/nickel molar concentration ratio, current density, citrate concentrations, plating temperature, and plating time, used to determine their influence on the polarization resistance and corrosion resistance. In steps 2 and 3 the significant variables were studied using the steepest ascent method and the central composite design (CCD) to find the most optimal conditions for zinc‐nickel electroplating. These conditions were found to be a Zn/Ni molar concentration ratio of 0.66, a plating temperature of 28 °C, an electroplating current density of 60 mA/cm 2, an electroplating time of 13 min, and a citrate concentration of 0.062 mol/L. The corrosion behaviour test of step 4 showed that the films with a higher intensity of the γ‐NiZn3, γ‐Ni2 Zn11, and γ‐Ni3 Zn22 phases exhibited better corrosion resistance.